Hospital Dentistry: challenges, epidemiological profile of patients, and competencies of the dental surgeon in the hospital setting - de Oliveira, Carlos Eraldo Gadelha; Alexandre, Ana Tafet Nascimento; Clementino, Herlon Alberto; de Oliveira, Ataide Matias; Oliveira da Silva, Maria Cláudia; Duarte Lins, Etiene Pereira; Verissimo, Rodolfo Scott; HUDSON GOMES DE SANTANA, ILAN (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: Hospital Dentistry has become established as a fundamental component of multidisciplinary teams, standing out due to the interface between oral health and systemic conditions in hospitalized patients. Objective: To critically analyze the challenges for consolidating Hospital Dentistry in Brazil, the epidemiological profile of the patients treated, and the competencies required of dental surgeons in the hospital setting. Methods: Narrative literature review, with searches conducted in PubMed, Scopus, LILACS, and SciELO databases, covering publications from 2010 to 2025. Original studies, systematic reviews, guidelines, and consensus documents directly addressing hospital dental practice were included. Results: A significant increase in scientific production on the topic was observed over the past fifteen years. The profile of hospitalized patients requiring dental care is characterized by high clinical complexity, predominantly involving immunosuppressed individuals, mechanically ventilated patients, oncology patients, and transplant recipients. Dental interventions have been shown to reduce infectious complications, such as ventilator-associated pneumonia, and to contribute to the management of oral manifestations of oncologic therapies. The competencies required of hospital dental surgeons include expanded knowledge of systemic pathophysiology, hospital pharmacology, management of critically ill patients, and strict adherence to biosafety and patient safety protocols. Conclusion: Despite regulatory advances and growing recognition of the importance of Hospital Dentistry, structural, educational, and organizational challenges still limit its universal implementation. Investments in public policies, specialized training, and evidence-based care protocols are essential to consolidate this practice as an integral part of hospital care.